Impact of glycosylated hemoglobin on early neurological deterioration in acute mild ischemic stroke patients treated with intravenous thrombolysis - Han, Lin; Hou, Zhangyan; Ma, Mingwei; Ding, Dongxue; Wang, Dapeng; Fang, Qi (Frontiers in Aging Neuroscience, 2023)
Objective: In patients with acute mild ischemic stroke treated with intravenous thrombolysis, the relationship between chronic hyperglycemic status and their early neurological deterioration (END) and clinical outcomes is unclear. We attempted to analyze the relationship between glycated hemoglobin (HbA1c) levels and END and 90-day functional outcomes. Participants and Methods: The research comprised 267 patients with acute mild ischemic stroke. The incidence of END and functional outcomes at 90 days were evaluated between subgroups. END was defined in this study as a rise of at least 1 point in the National Institutes of Health Stroke Scale (NIHSS) score within 72 hours of admission, with an excellent outcome of a modified Rankin Scale (mRS) score of 0-1 at 90 days following stroke beginning. The association between HbA1c and END, and clinical outcomes in patients with mild stroke, was assessed by logistic regression after adjusting for confounding factors. In addition, we used receiver operating characteristic (ROC) curves to predict the predictive value of HbA1c for the incidence of END. Results: There were 38 patients who suffered END and 105 patients who had disabled functional outcomes at 90 days. In multivariate analysis, elevated HbA1c levels were associated with END (adjusted OR = 1.476; 95% CI: 1.129-1.928; p = 0.004). With HbA1c greater than 7.75%, the ROC curve predicted a higher risk of END. However, they were not associated with patients' functional outcomes at 90 days. Conclusions: HbA1c levels were an independent predictor of END in patients with mild stroke, while there was no effect on functional outcomes at 90 days. The impact of HbA1c on functional prognosis may be a contributing factor rather than a direct factor.